AB1073 Accuracy Assessment of Remission Criteria in Relation to Ultrasound Findings in Hands and Feet in Patients with Rheumatoid Arthritis. (9th June 2015) - Martire, M.V.; Puente Trigo, D.; Duarte, V.M.; Marino Claverie, L.; Amaya Crespo, G.; Manzano, M.; Carlevaris, L.; Secco, A.; Mamani, M.
Abstract : Background: Currently, one of the main goals of rheumatoid arthritis treatment is to attain remission. Stricter criteria, namely CDAI, SDAI ACR/EULAR Boolean have been proposed. Moreover, DAS28 is criticized for the exclusion of foot joints assessment. However the degree of agreement that they have with the ultrasound findings in patienrs in remission is not well known. Objectives: The aim of our study is to evaluate the degree of agreement between the state of remission as measured by different stricter criteria and the absence of activity assessed by ultrasound of hands and toes. Methods: We included consecutive patients diagnosed with RA according to ACR EULAR 2010 criteria being in remission defined as DAS28 <2.6. We evaluated whether stricter criteria were met (CDAI, SDAI, Boolean, Boolean without EVA). A rheumatologist specialized in musculoskeletal ultrasound, who was unaware of the state of activity, performed ultrasonography on hands and toes. Systematic evaluation was performed on grayscale and power Doppler technique with multifrequency linear transducer (10-18MHz) in longitudinal and transverse sections of the radiocarpal joint, second and third metacarpophalangeal, second and third proximal interphalangeal in both hands and second to fifth articulation metatarsophalangeal (all of them bilateral). Lack of activity was defined when the patient had no exudative synovitis grade II and III, and power Doppler grade II and III in any of the evaluated joints. Results: 100 ultrasounds were performed in 100 patients, 80% were women (n=80) and the mean age was 52.7 DS 12. There were no differences in age, sex, duration of disease, treatment, or RF and antiCCO positivity between patients with and without ultrasound activity. Table 1 shows the state of remission of the evaluated patients. Table 2 shows the degree of agreement among different criteria, and the absence of activity assessed by ultrasound in hands and feet. Conclusions: There was no agreement between the state of remission measured by the various strict criteria and the absence of activity assessed by ultrasound feet in this study population. Only acceptable agreement was found with the Boolean criterion that excludes EVA on hands was found. References: Felson DT, Smolen JS, Wells G, Zhang B, van Tuyl LH, Funovits J, et al. American College of Rheumatology; European League Against Rheumatism. American College of Rheumatology/European League Against Rheumatism provisional definition of remission in rheumatoid arthritis for clinical trials. Arthritis Rheum. 2011; 63:573-86. Disclosure of Interest: None declared